From ritual to refuse : faunal exploitation by the elite of Chinikihá, Chiapas, during the Late Classic period - Montero López, Coral, (Archaeopress pre-Columbian archaeology ;, 2022)
'From Ritual to Refuse' explores the faunal exploitation by the Maya elite at the site of Chinikihá, Chiapas, during the end of the Late Classic period (AD 700-850) by applying zooarchaeological and statistical analyses to a faunal assemblage located in a basurero or midden behind a palatial structure at the core of the site.